Recent progress in the thermal and catalytic conversion of lignin. (September 2019) - Ha, Jeong-Myeong; Hwang, Kyung-Ran; Kim, Young-Min; Jae, Jungho; Kim, Kwang Ho; Lee, Hyung Won; Kim, Jae-Young; Park, Young-Kwon
Abstract: The issues over increases in energy demand and environmental pollution attributed to excessive use of fossil fuel have been the driving forces of the exploration for eco-friendly resource. Lignocellulosic biomass consisting of carbohydrates and lignin can be a renewable feedstock for replacing fossil fuels in the future because it is a plentiful and carbon neutral material. Especially, lignin, cross-linked phenolic polymers, is a topic of interest owing to its abundant production from pulp/paper industries as well as lignocellulose based biorefinery. The large potential of platform chemicals and biofuels from lignin has opened up an extensive range of opportunities to develop thermal and catalytic conversion technology. Over a few decades, several lignin conversion processes including catalytic pyrolysis, catalytic depolymerization, and catalytic oxidation have been developed to improve target products yields and to suppress side reactions. More recently, lignin-first approaches which maintain carbohydrates intact by selective extraction of lignin as valuable phenolics from whole biomass has been suggested. This review introduces recent ten years progress on thermal and catalytic conversion technology in terms of process type, catalyst development, and target products. This review is expected to offer an influential information for future research into the thermal and catalytic conversion of lignin as well as lignocellulosic feedstock. Highlights: Recent discoveries in thermal and catalytic lignin conversion are introduced. A proper conversion process should be considered depending on the lignin type. Catalyst plays a decisive role in product distribution and selectivity in process. The challenges and future perspective of each process is discussed.